Analyzing Online Lending In The Islamic Economy: Ethical Challenges And Fintech Innovations In Indonesia - Cahya Putri, Merly; Aeni, Nur; Sholekah, Aminatus (BIMA Journal (Business, Management, & Accounting Journal), 2024)
Purpose: This study aims to analyze the opportunities and challenges in implementing Sharia-compliant online lending models within Indonesia's Islamic fintech ecosystem, with strategic recommendations for sustainable development.Methodology: A qualitative approach was used, combining literature analysis, interviews with industry players, and evaluation of regulations. The focus was on assessing Sharia compliance and exploring best practices from global Islamic fintech ecosystems. Results: The findings reveal significant potential for Islamic fintech in promoting financial inclusion, particularly for underserved communities. However, challenges such as low Islamic financial literacy and inconsistent regulatory oversight hinder progress. Findings: Sharia-compliant contracts like qard hasan, musyarakah, and mudarabah show promise in addressing ethical concerns and fostering financial sustainability. Originality: This research provides a comprehensive evaluation of Sharia-compliant online lending models in Indonesia, incorporating global best practices. Novelty: The study highlights the strategic role of maqashid sharia principles in creating ethical and transparent fintech solutions. Conclusions: Strengthened regulations, public education, and innovation in contract models are essential for sustainable Islamic fintech development in Indonesia. Type of Paper: Conceptual research.